Direct and Simultaneous Identification of Multiple Mitochondrial Reactive Oxygen Species in Living Cells Using a SERS Borrowing Strategy. (21st April 2022) - Lin, Shichao; Ze, Huajie; Zhang, Xia‐Guang; Zhang, Yue‐Jiao; Song, Juan; Zhang, Huimin; Zhong, Han‐Liang; Yang, Zhi‐Lan; Yang, Chaoyong; Li, Jian‐Feng; Zhu, Zhi
Abstract: Identification of different mitochondrial reactive oxygen species (ROS) simultaneously in living cells is vital for understanding the critical roles of different ROS in biological processes. To date, it remains a great challenge to develop ROS probes for direct and simultaneous identification of multiple ROS with high specificity. Herein, we report a SERS‐borrowing‐strategy‐based nanoprobe (Au@Pt core–shell nanoparticles) for simultaneous and direct identification of different ROS by their distinct Raman fingerprints. Isotope substitution experiments and DFT calculations confirmed the ability of Au@Pt nanoprobe to capture and identify different mitochondrial ROS (i.e. ⋅OOH, H2 O2, and ⋅OH). When functionalized with triphenylphosphine (TPP), the Au@Pt‐TPP nanoprobe located to mitochondria and detected multiple ROS simultaneously in living cells under oxidative stimulation. Our method offers a new tool for the study of the functions of various ROS in biological processes. Abstract : A SERS‐borrowing‐strategy‐based Au@Pt core–shell nanoprobe (Au@Pt NP) was developed for simultaneous and direct spectroscopic detection and identification of multiple reactive oxygen species (ROS). Triphenylphosphine‐functionalized Au@Pt‐TPP NPs were able to locate to the mitochondria for the detection and identification of different mitochondrial ROS simultaneously in living cells under oxidative stress.